Time as a political resource: early greek thought and Plato`s philosophy of time = Czas jako środek polityczny - wczesna myśl grecka i filozofia czasu Platona - Pleshkov, Aleksei (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, the author reconstructs the intellectual context relevant to Plato`s "philosophy of time". First of all, since the tradition preceding Plato did not produce a unified concept of time, the problem of multiplicity of times is discussed. Then, the author examines the peculiar experience of the instability of time, linking dimensions of human behavior and cosmic order. Finally, the problem of affectivity of time and the need for standardizing time for political coexistence is considered. It is argued that the concept of time is what allows Plato to connect the micro-level of individual behavior with the meso-level of politics and macro-level of nature.
Keywords: czas; wieczność; filozofia czasu; wielość czasów; niestabilność czasu; afektywność czasu; wspólnota; polityka; Plato (filozof; 427 p.n.e.-347 p.n.e.); wczesna myśl grecka; time; eternity; philosophy of time; multiplicity of times; instability of time; affectivity of time; community; politics; early Greek thought